Flow-Induced Deformantions of a Compliant Insert in Channel Flow: from Small to Large Amplitudes - Lai, Lawrence; Lucey, Anthony; Elliott, Novak (ASME, 2012)
In this paper we consider a fluid-conveying channel with a compliant insert undergoing large amplitude flow-induced deformations. The objective is to assess the suitability of an open source finite element library oomph-lib for modelling this system. The fundamental system is relevant to a host of applicationsin both engineered (e.g. flexible-pipes, membrane filters, and general aero-/hydro-elasticity) and biomechanical (e.g. blood flow, airway flow) systems. The structural model uses a geometricallynonlinear formulation of the solid mechanics. Viscous flow is modelled at Reynolds numbers producing unsteady laminar flow. We present a brief summary of previous component validations with oomph-lib. We then focus on the unsteady-state FSI validation by comparing with published results, obtainedusing different computational schemes. This is done for both small-amplitude and large-amplitude wall deformations. Finally, we look at some preliminary energetics analysis of the flexible wall. The validations demonstrate the suitability and versatility of oomph-lib as a modelling and predictive tool. The flexible wall energetics validation show the possibility of understanding system stability through analysis of the flexible wall and fluid energetics.